Investigation of the antioxidant properties of Persea americana seed flour altered by the fermentation process with Lactobacillus plantarum - Kumari, Polegodage Dilushi Sureka Ruwan; Amarakoon, Ranjani; Gunarathna, Madushan Dhammika (European Journal of Chemistry, 2024)
This study aims to investigate the effect of Lactobacillus plantarum fermentation on the antioxidant potential of Persea americana seed flour. The half-maximal inhibitory concentration (IC50) value of avocado seed flour after fermentation for 24, 48, and 72 h was compared with the unfermented avocado seed flour using the measurement of free radical scavenging activity of 2,2-diphenyl-1-picrylhydrazyl (DPPH). Additionally, the change in pH value was measured to confirm the continuous fermentation process within the desired period. The results for the DPPH assay for unfermented, 24, 48, and 72 h fermented avocado seed flour were 61.5±0.71, 51.18±0.10, 46.00±0.21, 43.73±0.21 µg/mL, respectively, which indicated a significant increase (p < 0.05) of IC50 values of avocado seed flour with the fermentation. Furthermore, with the fermentation period, there was a significant decrease in the pH value for the 72-hour fermented sample (4.15±0.03) compared to the unfermented sample (6.81±0.04). These results supported avocado seed as an important by-product source for the further development of health-promoting products, by confirming the increased antioxidant capacity of avocado seed flour after fermentation.